Evaluating the abiotic synthesis potential and the stability of building blocks of life beneath an impact-induced steam atmosphere - Zhang, Zongbin; Jiang, Haofan; Ju, Pengcheng; Pan, Lu; Rouillard, Joti; Zhou, Gentao; Huang, Fang; Hao, Jihua (Frontiers in Microbiology, 2023)
A prerequisite for prebiotic chemistry is the accumulation of critical building blocks of life. Some studies argue that more frequent impact events on the primitive Earth could have induced a more reducing steam atmosphere and thus favor widespread and more efficient synthesis of life building blocks. However, elevated temperature is also proposed to threaten the stability of organics and whether life building blocks could accumulate to appreciable levels in the reducing yet hot surface seawater beneath the steam atmosphere is still poorly examined. Here, we used a thermodynamic tool to examine the synthesis affinity of various life building blocks using inorganic gases as reactants at elevated temperatures and corresponding steam pressures relevant with the steam-seawater interface. Our calculations show that although the synthesis affinity of all life building blocks decreases when temperature increases, many organics, including methane, methanol, and carboxylic acids, have positive synthesis affinity over a wide range of temperatures, implying that these species were favorable to form (>10-6 molal) in the surface seawater. However, cyanide and formaldehyde have overall negative affinities, suggesting that these critical compounds would tend to undergo hydrolysis in the surface seawaters. Most of the 18 investigated amino acids have positive affinities at temperature < 220 °C and their synthesis affinity increases under more alkaline conditions. Sugars, ribose, and nucleobases have overall negative synthesis affinities at the investigated range of temperatures. Synthesis affinities are shown to be sensitive to the hydrogen fugacity. Higher hydrogen fugacity (in equilibrium with FQI or IW) favors the synthesis and accumulation of nearly all the investigated compounds, except for HCN and its derivate products. In summary, our results suggest that reducing conditions induced by primitive impacts could indeed favor the synthesis/accumulation of some life building blocks, but some critical species, particularly HCN and nucleosides, were still unfavorable to accumulate to appreciable levels. Our results can provide helpful guidance for future efforts to search for or understand the stability of biomolecules on other planets like Mars and icy moons. We advocate examining craters formed by more reducing impactors to look for the preservation of prebiotic materials.